Neoproterozoic/Lower Palaeozoic geodynamic evolution of Dronning Maud Land: integrating geology and geophysics - Jacobs, Joachim; Läufer, Andreas; Clark, Chris; Kleinhanns, Ilka; Elburg, Marlina; Ruppel, Antonia; Estrada, Solveig; Damaske, Detlef; Jokat, Wilfried; Riedel, Sven; Lucka, Nicole (Changing polar regions : 25th International Congress on Polar Research ; March 17-22, 2013, Hamburg, Germany, 2013)
East Antarctica probably formed by amalgamation of a number of cratons along distinct Ediacaran mobile belts, including the ca. 600-500 Ma East African-Antarctic Orogen (EAAO) that dissects Dronning Maud Land (DML). New field-work during the international expeditions Geodynamic Evolution of East Antarctica (GEA) I + II in the austral summers 2010/11 and 2011/12, and first geochronological results from eastern DML reveal a complex tectonic architecture across the belt. In western DML, the EAAO reworks older Mesoproterozoic crust of the Maud Belt; the westernmost boundary of the mobile belt is characterized by a major dextral transpressional shear zone. In central DML, a major magnetic anomaly, the Forster anomaly, was interpreted as a cryptic suture of the EAAO (Riedel et al. 2012). The area where the Forster anomaly crosses the DML mountains is poorly investigated so far, but appears to coincide with a major strike slip shear zone in the southern Kurze Mts. and the occurrence of major Ediacaran granulite bodies. East of the Forster anomaly, the magnetic anomaly pattern changes significantly and typical Maud type crust is not present any longer. GEA II targeted a range of nunataks between Sør Rondane and central DML that had never been visited previously (from Blåklettane and Bergekongen in the E to Urna and Sørsteinen in the W). These nunataks are dominated by medium- to high-grade metasedimentary and metavolcanic rocks of possibly Neoproterozoic age, including abundant marble and graphite schists. Sør Rondane in eastern DML, is dominated by two distinct blocks separated by the dextral Main Shear Zone. The northwestern block is still part of the eastern EAAO, where new SHRIMP zircon data from metamorphic rims provide ages of ca. 560 Ma. The southeastern block is made up of a TTG terrane, which provides four new SHRIMP zircon dates between 990-980 Ma, interpreted as igneous crystallization ages (oceanic arc). The TTG terrane shows limited tectonic overprint and is likely the southeastern foreland of the EAAO. Close to the contact of the two blocks grey geisses and augen-gneisses gave zircon crystallization ages of ca. 750 Ma, ages which were previously unknown from the EAAO. The Forster anomaly therefore separates distinctly different parts of the EAAO: a) a reworked, mainly Grenville-age crust to the W (the overprinted margin of the Kalahari Craton) and b) a part of the orogen dominated by Neoproterozoic accretionary tectonics to the E. This difference is also reflected in the geochemistry of voluminous late-tectonics granitoids across the belt.
Keywords: Dronning Maud Land; geofysikk; geologi

Low frequency variability on the continental slope of the southern Weddell Sea - Jensen, Mari F; Fer, Ilker; Darelius, Elin (Journal of Geophysical Research: Oceans, 2013)
One-year long records of temperature, salinity, and currents show seasonally varying, energetic oscillations with a dominant period of approximately 35 h on the upper continental slope of the southern Weddell Sea. The data set is sampled by five moorings deployed on the slope of the Crary Fan, east of the main outflow site of the Filchner overflow plume. The characteristics of the observed oscillations are compared to idealized coastal trapped waves inferred from a numerical code. The variability at 35 h period is identified as mode 1 waves with wavelengths less than 200 km and group velocity opposing the phase speed, indicating energy propagation toward east. Filchner Depression and the nearby ridges on the slope are suggested as the generation site where the dynamics associated with the overflow plume can force the variability. Historical time series at the overflow site are revisited to identify the source of previously reported variability at 3 and 6 day time scales. Mode 2 waves at wavelengths of about 100 and 1000 km were found to bear resemblance to the 3 day and 6 day variability, respectively. The seasonal variation in the energy in the 35 h band shows small but significant correlation with the low frequency easterly winds. The presence of coastal trapped waves along the continental slope of the Weddell Sea can increase the heat exchange across the shelf break and affect the dense water production rates.
Keywords: Sørishavet; Weddellhavet; batymetri; bunnvann; geofysikk; havstrømmer; kelvinbølger; saltinnhold; temperatur måling

Electrical structure beneath Schirmacher Oasis, East Antarctica: a magnetotelluric study - Murthy, D N; Veeraswamy, K; Harinarayana, T; Singh, U K; Santosh, M (Polar Research, 2013)
Maitri Station (70.76°S; 11.73°E) is located in Schirmacher Oasis, a coastal nunatak in north-central Dronning Maud Land covering an area of 35 km2. Here, we report results from the first magnetotelluric experiments and delineate the deep electrical conductivity structure under Schirmacher Oasis using the data acquired during the 24th Indian Antarctic Scientific Expedition. The magnetotelluric method has the advantage of shallow to deeper level coverage as the data acquisition covers a wide frequency band of 10-3103 Hz, permitting different penetration depths depending on the frequency and conductivity of the layer under investigation. The modelling results indicate the presence of a highly resistive (8000-10 000 ohm m) upper crust, which shows a lateral variation in thickness from 20 km (below site 6) in the east to 10 km (between sites 1 and 2) in the west. It is underlain by a less resistive (500-600 ohm m) lower crust. The highly resistive upper crustal structure supports the existing notion that western Dronning Maud Land is a stable, cratonic platform. Results of free-air gravity, seismic, geomagnetic and surface wave dispersion investigations in East Antarctica also indicate a cratonic-type crust. The results of our study allow us to identify a westward thinning of the upper crust with a marked boundary between sites 1 and 2. We also find evidence for the continuity of the Mozambique mobile belt in East Antarctica on the western side of Schirmacher Oasis. Keywords: Magnetotellurics; Schirmacher Oasis crustal structure; East Antarctica; Mozambique Belt; electrical conductivity.
Keywords: Dronning Maud Land; geofysikk; geologi; magnetotelluriske eksperimenter